Association between hypothyroidism and risk of chronic kidney disease: evidence from a systematic review and meta-analysis - Zhuang, Wei-Kun; Hu, Xin-Yu; An, Yun-Jia; Liu, De-Liang; Li, Hui-Lin (Frontiers in Endocrinology, 2026)
BackgroundChronic kidney disease (CKD) has become a significant issue in global public health, with its prevalence showing a persistent upward trend. Traditional risk factors cannot fully explain the persistent increase in incidence rates. Hypothyroidism, a common endocrine disorder, is considered a potential non-traditional risk factor for CKD, but the evidence remains inconsistent. This study aims to systematically evaluate the association between hypothyroidism and CKD risk.MethodsSearch PubMed, Embase, Web of Science, and Cochrane Library databases for relevant literature up to September 1, 2025. Included observational studies reporting the association between overt or subclinical hypothyroidism and CKD risk, providing odds ratios (OR) or hazard ratios (HR) with 95% confidence intervals (CIs). Quality assessment was conducted using the Newcastle–Ottawa Scale (NOS) and the Agency for Healthcare Research and Quality (AHRQ) quality assessment tool. Calculate pooled risk estimates using random-effects models, and conduct subgroup analyses, sensitivity analyses, and publication bias analyses.ResultsA total of 13 publications reporting 15 studies (11 cross-sectional and 4 cohort studies) involving approximately 5,101,102 participants were included. The pooled analysis of cross-sectional studies demonstrated that hypothyroidism was significantly associated with CKD (OR = 1.66, 95% CI: 1.43–1.94; I² = 78.6%). Subgroup analyses revealed consistent associations across different thyroid disease types, regions, diagnostic methods, and study quality group. Pooled results from cohort studies also demonstrated that hypothyroidism significantly increased CKD risk (HR = 1.21, 95% CI 1.08-1.36; I² = 50.08%). Sensitivity analysis results remained stable. Publication bias was present in cross-sectional studies, but the association remained significant after using the trim-and-fill method (adjusted OR = 1.29, 95% CI: 1.06–1.57).ConclusionThis systematic review and meta-analysis suggests that hypothyroidism is associated with an increased risk of CKD. Future well-designed prospective and interventional studies are needed to clarify temporal and causal relationships and to elucidate the underlying mechanisms between hypothyroidism and renal dysfunction.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251143834.